The face of Tutankhamun (British Broadcasting Corp., 1992)
This four volume documentary traces archaeologist Howard Carter's beginnings in rural England to the Valley of the Kings. It presents the story of Tutankhamun from the moment of Carter's discovery to the current problems modern civilization faces in trying to preserve the treasures for future generations. It also shows how the excavation made Tutankhamun a pivotal cultural icon of the twentieth century.